Tuning the Optoelectronic Properties of Perylene Diimide for Advanced Organic Photovoltaic - Ali Raza Ayub; Muhammad Sabir; Salba; Umer Yaqoob; Karim Youssef Nabat; Hui Li (Energy Technology, 2026)
Organic solar cells (OSCs) are becoming more popular because they are cheap to make, flexible, and have a higher power conversion efficiency (PCE), which has gone up from 4.1% in 2010–25.21% in 2022. However, making the active layer materials’ electrical characteristics better is still a big problem when it comes to getting even more efficient. This research seeks to tackle this problem by creating and synthesizing a group of small molecules (PDI‐1 to PDI‐6) using a perylene diimide indacenodithiophene (PIDT) acceptor structure and adding different donor–acceptor connectors to improve charge transfer and light absorption.We tested their photovoltaic performance and compared it to that of a reference molecule (PDI‐R). All synthesized molecules exhibit low bandgaps, higher dipole moments, and improved electron transfer properties. Among them, PDI‐4, a donor–acceptor–donor (D–A–D) structured molecule with a thiophene bridge, demonstrated the best overall performance, showing enhanced π ‐delocalization and charge–transfer efficiency. These findings contribute to the broader goal of advancing the molecular design of active‐layer materials for high‐performance OSCs.
Keywords: Organic Electronics and Photovoltaics; Perovskite Materials and Applications; Conducting polymers and applications